2018
DOI: 10.1111/apm.12902
|View full text |Cite
|
Sign up to set email alerts
|

WHO laboratory validation of Xpert® CT/NG and Xpert® TV on the GeneXpert system verifies high performances

Abstract: Effective tests for diagnosis of sexually transmitted infections ( STI s), used point of care to inform treatment and management decisions, are urgently needed. We evaluated the analytical sensitivity and specificity of the Xpert ® CT / NG and Xpert ® TV tests, examining 339 samples spiked with phenotypically and/or genetically diverse strains of Neisseria gonorrhoeae , … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 17 publications
0
29
0
Order By: Relevance
“…For example, the frequency of resistant strains in a study of over 4500 isolates from six Asian countries was found to be 0.17% [60]. Most often, this type of research does not detect resistant strains [4,24,120].…”
Section: Resistance To Spectinomycinmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the frequency of resistant strains in a study of over 4500 isolates from six Asian countries was found to be 0.17% [60]. Most often, this type of research does not detect resistant strains [4,24,120].…”
Section: Resistance To Spectinomycinmentioning
confidence: 99%
“…Several bacterial or viral diseases can be transmitted simultaneously that may need the adequate diagnostics and therapy [2,3]. Gonorrhoea diagnostics can be carried out using both culture and molecular methods, but bacterial culture is necessary to determine drug susceptibility [4,5]. According to the WHO data, the number of gonorrhoea patients amounted to over 78 million people per year [6], and this value may be greatly underestimated considering a relative ease of treatment and incomplete registration of infections in many countries.…”
Section: Introductionmentioning
confidence: 99%
“…Gonorrhoea cases have been risen worldwide over the last decades, especially in the well-developed countries ( 3 ). Use of highly sensitive and specific molecular tests and genome-based technics lead to effective screening and diagnostic efforts ( 16 ). In less-developed countries, for example, in Ukraine, microscopy and culture remain to be basic laboratory methods for screening and diagnosing gonorrhoea.…”
Section: Discussionmentioning
confidence: 99%
“…The present study, for the first time, investigated the prevalence of CT, NG and TV using highly sensitive and specific US FDA-approved NAATs (Aptima Combo 2 and Aptima TV assays (Hologic); (6,7,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)30)) for consecutive mainly symptomatic sexually active females and males in Ukraine (Ternopil) and evaluated the CDTs used for diagnosis of these non-viral STIs compared to the reference Aptima NAATs.…”
Section: Discussionmentioning
confidence: 99%
“…For detection of Chlamydia trachomatis (CT), Neisseria gonorrhoeae (NG) and Trichomonas vaginalis (TV), NAATs have superior sensitivities, high specificities, use non-invasive specimens, are rapid and provide opportunities for automation (8)(9)(10)(12)(13)(14)(15)(16)(17)(18)(19)(20). The sensitivities and specificities of the US FDAapproved Aptima NAATs (Hologic, San Diego, CA, USA) for detection of CT, NG and TV have proven excellent (7,(16)(17)(18)(19)(20)(21)(22)(23)(24), and these NAATs have been frequently used as gold standard diagnostic tests to evaluate other diagnostic assays (6,7,20,25,26). However, in many less-resourced settings, which frequently suffer from the highest prevalences of non-viral STIs, the validated and quality-assured US FDAapproved NAATs are not affordable (4,5,14,27).…”
mentioning
confidence: 99%